Generalization of negatively reinforced mands in children with autism. Issue 3 (4th August 2014) - Groskreutz, Nicole C.; Groskreutz, Mark P.; Bloom, Sarah E.; Slocum, Timothy A.
<x xml:space="preserve">Abstract</x> Each day, people encounter stimuli they find unpleasant. Some children with autism may require systematic instruction to acquire the communication skills necessary to request the termination of such aversive stimuli. We taught 2 school‐aged boys with autism a mand (e.g., signing "stop") that could be used to escape a variety of aversive stimuli. First, we employed a systematic assessment to identify aversive stimuli to use during training. We then conducted mand training sequentially across those stimuli until sufficient exemplars were trained for generalization to occur to untrained stimuli. For both participants, cross‐stimulus generalization was observed after training with 2 stimuli. Participants manded for escape in the presence of aversive stimuli, but almost never manded in the presence of preferred stimuli or when the programmed stimuli were absent. In addition, we found an inverse relation between acquisition of the mand and engagement in problem behavior and evidence of generalization to nontraining contexts.